SURFACE COMPLEXATION OF PB(II) AT OXIDE-WATER INTERFACES: I. XAFS AND BOND-VALENCE DETERMINATION OF MONONUCLEAR AND POLYNUCLEAR PB(II) SORPTION PRODUCTS ON ALUMINUM OXIDES - Bargar J.R.; Brown G.E.; Parks G.A. (My University, 1997)
Pb(II) sorption on Al2O3 powders was studied as functions of sorption density (from 0.5 to 5.2 μmoles/m2) and [Pb]eq (0.03-1.4 mM) in 0.1 M NaNO3 electrolyte solution using XAFS spectroscopy. At pH 6 and 7, Pb(II) ions were found to be fully hydrolyzed and adsorbed preferentially as mononuclear bidentate complexes to edges of AlO6 octahedra. At higher sorption densities (Γ =< 3.4 μmoles . m-2), XAFS results suggest the presence of dimeric Pb(II) surface complexes. A bond-valence model was used in conjunction with these results to constrain the compositions and reaction stoichiometries of adsorption complexes. We conclude that Pb(II) adsorption on alumina is attributable to complexation by [AlAlAl???O-12] and [Al-OH-12] surface functional groups. Several plausible Pb(II) adsorption reactions are proposed, based on these results, which provide a basis for chemically realistic descriptions of surface complexation of Pb(II) on aluminum oxides.